Nonconventional Markers of Sepsis - Kustán, Péter (EJIFCC, 2017)
Sepsis still remains a challenging healthcare problem with high mortality rate. To improve outcome, early diagnosis and monitoring of sepsis is of utmost importance. In this process objective laboratory parameters are the most helpful. Procalcitonin and C-reactive protein are the most commonly used and recommended markers of sepsis however, more than 200 sepsis biomarkers have already been published. This mini review focuses on nonconventional novel possibilities for the recognition of sepsis severity. Presepsin, actin and actin scavenger proteins (gelsolin and Gc-globulin) and orosomucoid are discussed. Besides serum parameters, the urinary levels of these markers are also elaborated, since urinary biomarkers of sepsis provide new diagnostic implications and are helpful for monitoring both the kidney function and the septic process. Increasing serum actin levels and decreasing levels of actin binding proteins seem to be associated with sepsis severity and outcome. Actin can be detected in the urine samples of septic patients as well, and strongly elevated levels of it were found in sepsis-related acute kidney injury. Both serum and urinary orosomucoid might be able to indicate sepsis, however urinary orosomucoid is a more sensitive inflammatory marker. Novel laboratory tests can provide rapid help for clinical decision making because the key point in successful treatment lies in the early diagnosis of sepsis.